Characterization of HIV-2 susceptibility to protease and entry inhibitors and identification of envelope determinants of coreceptor usage, cell tropism and antibody neutralization - Martins, Andreia Rodrigues, 1983- (2018)
Tese de doutoramento, Farmácia (Microbiologia), Universidade de Lisboa, Faculdade de Farmácia, 2018